McEvoy, Carmen (ed.). Funerales republicanos en América del Sur: tradición, ritual y nación, 1832-1896. Santiago de Chile: Centro de Estudios Bicentenario/Instituto de Historia, Pontificia Universidad Católica de Chile, 2006, 258 pp. - Aljovín de Losada, Cristóbal (2006)
La reseña no presenta resumen.